Enhance transgene responses through improving cellular uptake and intracellular trafficking by bio-inspired non-viral vectors - Ma, Xi-Xi (J Nanobiotechnology, 2020)
BACKGROUND: Gene therapy remains a significant challenge due to lots of barriers limiting the genetic manipulation technologies. As for non-viral delivery vectors, they often suffer insufficient performance due to inadequate cellular uptake and gene degradation in endosome or lysosome. The importance of overcoming these conserved intracellular barriers is increasing as the delivery of genetic cargo. RESULTS: A surface-functionalized non-viral vector involving the biomimetic mannitol moiety is initiated, which can control the cellular uptake and promote the caveolae-mediated pathway and intracellular trafficking, thus avoiding acidic and enzymatic lysosomal degradation of loaded gene internalized by clathrin-mediated pathway. Different degrees of mannitol moiety are anchored onto the surface of the nanoparticles to form bio-inspired non-viral vectors and CaP-MA-40 exhibits remarkably high stability, negligible toxicity, and significantly enhanced transgene expression both in vitro and in vivo. CONCLUSIONS: This strategy highlights a paradigmatic approach to construct vectors that need precise intracellular delivery for innovative applications.